An Investigation of Definite Article as Fossilized Errors: Analysis of Classroom Presentations of EAP Students - Amin, Muhammad Waqar; Arshad, Hafiza Kashaf; Raza-E- Mustafa (ACADEMIA International Journal for Social Sciences, 2025)
This study aims to investigate the errors committed by EAP students and for that purpose classroom presentations of the students of BS English are recorded and transcribed to compile a corpus for convenience of sampling and analysis. This prompts the current study to adopt convenient sampling technique and data is processed via antconc to get concordance which has definite article as key inventory. For complete elaboration of the data, qualitative approach is adopted and for theoretical framework Selinker’s theory of Interlanguage is followed. The findings of the study prove that EAP learners overgeneralize the rules as they either use definite article with proper nouns or use them in repeated sequences. The repetition is of two types that is consecutive repetition and repetition with different nouns. This study is beneficial for EAP teachers and also leaves research gaps for the researchers as well as they can compare written and spoken samples in future.